Recurrent pregnancy loss: couples' perspectives on their need for treatment, support and follow up. Issue 2 (15th December 2018) - Koert, E; Malling, G M H; Sylvest, R; Krog, M C; Kolte, A M; Schmidt, L; Nielsen, H S
Abstract: STUDY QUESTION: What do couples referred to or attending a recurrent pregnancy loss (RPL) clinic believe they need in terms of treatment, support and follow up? SUMMARY ANSWER: Men and women wish for more information, earlier access to treatment, support and follow up that is sensitive to their history of pregnancy loss (PL), includes both members of the couple, and acknowledges the psychological impact of RPL. WHAT IS KNOWN ALREADY: Previous research has highlighted women's dissatisfaction with medical care provided post-PL and their desire for medical professionals to have increased awareness about PL and recognition of the psychological impact of PL. Less is known about the needs of the male partner, the needs of those experiencing RPL and whether the needs differ during different reproductive stages. STUDY DESIGN, SIZE, DURATION: Over a 2-month period in 2017–2018, 13 couples who were referred to the national RPL program in Copenhagen, Denmark were qualitatively interviewed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Inclusion criteria were heterosexual couples with at least three consecutive PLs before 12 weeks' gestation with no children or one child prior to the PLs, not currently pregnant, and willing to be interviewed in English. Couples were interviewed together in a semi-structured format. Data were analyzed using thematic analysis. Invitations ( n = 30) were sent to couples recently referred to the RPL program who indicated an interest in participating and 17 couples contacted the interviewer to schedule an interview. Due to cancellations, 15 interviews were held. Data from 13 interviews that met the study criteria were used for the current analysis. MAIN RESULTS AND THE ROLE OF CHANCE: The participants had experienced a median of three PLs (range 3–6). Both men and women described the cumulative effect of RPL with an increase in pressure and exhaustion by the third and subsequent losses. Inclusion of the male partner in consultations and treatment was seen as important. Men felt pressured to remain positive and support their partners despite their own feelings of loss. The findings showed that couples desired reliable and accurate information about RPL. They wished for recognition from the medical community that RPL has a significant psychological impact, and stressed that effective treatment should include both members of the couple, with attention to both physical and psychological aspects of the RPL and should be tailored to their current reproductive stage, in order to help them cope with the negative impact of RPL and the anxiety associated with conception and another pregnancy. LIMITATIONS, REASONS FOR CAUTION: Participants were self-selected thus findings cannot be generalized to all couples with RPL. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study addressing the needs of the female and male partners in couples suffering from RPL. The findings highlight a disconnect between couples' perceived needs and their experience of medical care after RPL. This may be partly due to a discrepancy in couples' and medical professionals' perceptions of the PLs. The findings highlight that medical professionals need to take a holistic and couple-focused approach in their treatment of RPL and include attention to the psychological impact and cumulative effect of the multiple PLs on the couple. The results underscore the need for informational resources and psychological support for couples experiencing RPL, tailored to their reproductive stage. STUDY FUNDING/COMPETING INTEREST(S): EK was funded by a Travel/Training Fellowship from ReproUnion, co-financed by the European Union, Interreg V ÖKS. No other competing interests were declared. TRIAL REGISTRATION NUMBER: N/A.